Fenceline on SGS with OTC in distance - Milchunas, Daniel, photographer (Colorado State University. Libraries, 2007)
View probably of ungrazed/grazed pastures near ARS HQ on SGS with open-top chambers in distance.
Keywords: experiments; grazing; SGS; shrublands; landscapes